An economic impact assessment of the use of earth observation information in flood hazard communication - Richard Bernknopf; Yusuke Kuwayama; Benjamin Zaitchik; Matthew Rodell; Augusto Getirana; Andrea Thorstensen; Samiha Shahreen (Natural Hazards, 2025)

An Abrupt Decline in Global Terrestrial Water Storage and Its Relationship with Sea Level Change - Matthew Rodell; Anne Barnoud; Franklin R. Robertson; Richard P. Allan; Ashley Bellas-Manley; Michael G. Bosilovich; Don Chambers; Felix Landerer; Bryant Loomis; R. Steven Nerem; Mary Michael O’Neill; David Wiese; et al. (Surveys in Geophysics, 2024)
As observed by the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow On (GRACE-FO) missions, global terrestrial water storage (TWS), excluding ice sheets and glaciers, declined rapidly between May 2014 and March 2016. By 2023, it had not yet recovered, with the upper end of its range remaining 1 cm equivalent height of water below the upper end of the earlier range. Beginning with a record-setting drought in northeastern South America, a series of droughts on five continents helped to prevent global TWS from rebounding. While back-to-back El Niño events are largely responsible for the South American drought and others in the 2014–2016 timeframe, the possibility exists that global warming has contributed to a net drying of the land since then, through enhanced evapotranspiration and increasing frequency and intensity of drought. Corollary to the decline in global TWS since 2015 has been a rise in barystatic sea level (i.e., global mean ocean mass). However, we find no evidence that it is anything other than a coincidence that, also in 2015, two estimates of barystatic sea level change, one from GRACE/FO and the other from a combination of satellite altimetry and Argo float ocean temperature measurements, began to diverge. Herein, we discuss both the mechanisms that account for the abrupt decline in terrestrial water storage and the possible explanations for the divergence of the barystatic sea level change estimates.

Using Satellite-Based Terrestrial Water Storage Data: A Review - Vincent Humphrey; Matthew Rodell; Annette Eicker (Surveys in Geophysics, 2023)
Land water storage plays a key role for the Earth’s climate, natural ecosystems, and human activities. Since the launch of the first Gravity Recovery and Climate Experiment (GRACE) mission in 2002, spaceborne observations of changes in terrestrial water storage (TWS) have provided a unique, global perspective on natural and human-induced changes in freshwater resources. Even though they have become much used within the broader Earth system science community, space-based TWS datasets still incorporate important and case-specific limitations which may not always be clear to users not familiar with the underlying processing algorithms. Here, we provide an accessible and illustrated overview of the measurement concept, of the main available data products, and of some frequently encountered technical terms and concepts. We summarize concrete recommendations on how to use TWS data in combination with other hydrological or climatological datasets, and guidance on how to avoid possible pitfalls. Finally, we provide an overview of some of the main applications of GRACE TWS data in the fields of hydrology and climate science. This review is written with the intention of supporting future research and facilitating the use of satellite-based terrestrial water storage datasets in interdisciplinary contexts.

Groundwater storage change detection from in situ and GRACE-based estimates in major river basins across India - Soumendra N. Bhanja; Abhijit Mukherjee; Matthew Rodell (Hydrological Sciences Journal, 2020)

Earth Observations and Integrative Models in Support of Food and Water Security - Stephanie Schollaert Uz; Alex C. Ruane; Bryan N. Duncan; Compton J. Tucker; George J. Huffman; Iliana E. Mladenova; Batuhan Osmanoglu; Thomas R. H. Holmes; Amy McNally; Christa Peters-Lidard; John D. Bolten; Narendra Das; et al. (Remote Sensing in Earth Systems Sciences, 2019)

Erratum to: Groundwater Storage Changes: Present Status from GRACE Observations - Jianli Chen; James S. Famiglietti; Bridget R. Scanlon; Matthew Rodell (Surveys in Geophysics, 2016)

Groundwater Storage Changes: Present Status from GRACE Observations - Jianli Chen; James S. Famigliett; Bridget R. Scanlon; Matthew Rodell (Surveys in Geophysics, 2016)

Estimating groundwater storage changes in the Mississippi River basin (USA) using GRACE - Matthew Rodell; Jianli Chen; Hiroko Kato; James S. Famiglietti; Joe Nigro; Clark R. Wilson (Hydrogeology Journal, 2007)